Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1073/pnas.95.14.7993
|View full text |Cite
|
Sign up to set email alerts
|

Gp91 phox is the heme binding subunit of the superoxide-generating NADPH oxidase

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
157
2
4

Year Published

2000
2000
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(171 citation statements)
references
References 44 publications
(47 reference statements)
8
157
2
4
Order By: Relevance
“…The deduced sequences contain conserved features considered critical for NADPH oxidase function (1), namely six hydrophobic segments within the N-terminal segment, proposed as membrane-embedded domains involved in transmembrane electron transport, as well as sequence motifs corresponding to proposed binding sites for heme, flavin, and NADPH. The third and fifth hydrophobic segments each contain two conserved histidines, which are thought to serve as coordination sites for two heme moieties within the corresponding sequences of gp91 phox and ferric reductase (13,14). Other sites exhibiting high homology occur within the C-terminal portion, corresponding to gp91 phox sequences that are thought to represent binding sites for flavin and NADPH (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The deduced sequences contain conserved features considered critical for NADPH oxidase function (1), namely six hydrophobic segments within the N-terminal segment, proposed as membrane-embedded domains involved in transmembrane electron transport, as well as sequence motifs corresponding to proposed binding sites for heme, flavin, and NADPH. The third and fifth hydrophobic segments each contain two conserved histidines, which are thought to serve as coordination sites for two heme moieties within the corresponding sequences of gp91 phox and ferric reductase (13,14). Other sites exhibiting high homology occur within the C-terminal portion, corresponding to gp91 phox sequences that are thought to represent binding sites for flavin and NADPH (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, it has been extensively demonstrated that the interaction of p22phox with Nox2 is required to form a functionally active enzyme in leukocytes (5). Recently, it was also demonstrated that co-transfection of p22phox together with Nox1 is required to facilitate Nox1-mediated O 2 Ϫ generation in CHO-cells, which reportedly lack endogenous p22phox expression (16).…”
Section: Discussionmentioning
confidence: 99%
“…The anchoring of the hemes in the cytochrome b 558 occurs via four histidines located at positions 101, 115, 209, and 222 in Nox2 (5). Mutation of any of these histidines, resulting in the loss of a heme in Nox2, leads to a conformational change in the protein and not only prevents O 2 Ϫ formation but also disrupts the interaction of Nox2 with p22phox (6).…”
mentioning
confidence: 99%
“…Although the topology and functions of plant rboh proteins have not been tested experimentally, several features of the amino acid sequence and comparisons with human gp91 phox allow predictions (Yu et al, 1998). NbrbohA and NbrbohB proteins are predicted to have six transmembrane-spanning domains (TMD-1 to TMD-6) that correspond to those identified in gp91 phox .…”
Section: Two Cdnas For the Gp91 Phox Homolog In N Benthamianamentioning
confidence: 99%